Parenting influences on adolescent sexual risk-taking: Differences by child welfare placement status. (January 2019) - Potter, Marina Haddock; Font, Sarah A.
Abstract: Positive parenting behaviors and parent-child relationships reduce sexual risk-taking among youth, but these associations may differ for adolescents in the child welfare system. Using two cohorts of a national longitudinal dataset of youth, the authors employed linear probability modeling to investigate associations of caregiver-child closeness, monitoring, and dating communication with youth's sexual initiation, sexual partners, and unprotected intercourse over the subsequent 12 months. Moderation by placement status (non-relative foster care, kinship care, or birth parent care) was then tested. Closeness was negatively associated with risk-taking. Monitoring was positively associated with new sexual partners among youth in birth parent care, but negatively associated with new partners for youth in out-of-home care. Dating communication was positively associated with sexual initiation and additional sexual partners, and with unsafe sex among non-relative foster youth. In sum, caregiver relationships and parenting behaviors may matter differently for maltreated and foster youths' sexual risk-taking. Highlights: Close caregivers reduce sexual risk-taking for youth in the Child Welfare System. Monitoring predicts more sexual partners for youth in birth parent care. Monitoring predicts fewer sexual partners for youth in out-of-home care. Dating communication is positively associated with sexual initiation and partners. Dating communication positively predicts unsafe sex among foster youth.